Homo Forte: A Philosophical Tribute to Muscle. Issue 4 (2nd October 2018) - Kretchmar, Scott
ABSTRACT: In this paper, I argue from a holistic standpoint for the intimate relationship between people and their muscles. While this stands as a direct tribute to muscle, it also serves as an acknowledgment of the work of Bill Morgan who championed multidisciplinary perspectives when analyzing philosophic issues. I honor and expand upon Morgan's recommendations by discussing cultural, biological, and philosophical insights related to persons and their musculature. I review the 'poor treatment' typically accorded muscles and then rally an interdisciplinary apologetic—one that ranges from the body philosophy of Marcel and Merleau-Ponty to evolutionary biology and systems theory. I conclude with speculations about the uncertain future of muscle for human existence and well-being.